2011
DOI: 10.1021/jf2040675
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Potential of Hesperetin Metabolites Obtained from Hesperetin-Administered Rat Serum: An Ex Vivo Approach

Abstract: In recent years much attention has been focused on the pharmaceutical relevance of bioflavonoids, especially hesperidin and its aglycon hesperetin in terms of their antioxidant and anti-inflammatory actions. However, the bioactivity of their metabolites, the real molecules in vivo hesperetin glucuronides/sulfates produced after ingestion, has been poorly understood. Thus, the study using an ex vivo approach is aimed to compare the antioxidant and anti-inflammatory activities of hesperidin/hesperetin or hespere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
91
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 45 publications
3
91
0
2
Order By: Relevance
“…Elucidating the transport mechanisms for phase II conjugates (sulfates and glucuronides) of hesperidin assumes great importance because 1) these hydrophilic conjugates are the main circulating metabolites; and 2) the conjugates possess many types of biologic activities, such as antioxidant and anti-inflammatory effects (Proteggente et al, 2003;Trzeciakiewicz et al, 2010;Yang et al, 2012;Yamamoto et al, 2013;Gamo et al, 2014). It has been shown that multiple transporters (BCRP, MRP2, and MRP3) are potentially responsible for efflux transport of hesperetin glucuronides (Brand et al, 2008(Brand et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the transport mechanisms for phase II conjugates (sulfates and glucuronides) of hesperidin assumes great importance because 1) these hydrophilic conjugates are the main circulating metabolites; and 2) the conjugates possess many types of biologic activities, such as antioxidant and anti-inflammatory effects (Proteggente et al, 2003;Trzeciakiewicz et al, 2010;Yang et al, 2012;Yamamoto et al, 2013;Gamo et al, 2014). It has been shown that multiple transporters (BCRP, MRP2, and MRP3) are potentially responsible for efflux transport of hesperetin glucuronides (Brand et al, 2008(Brand et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of anti-inflammatory activity, Yang et al reported that at 1-10 μM (0.3 – 3.02 μg/mL) HT concentrations, cellular levels of COX-2 and PEG2 are markedly attenuated [44]. With both the 10% and 20 %w/w films, HT levels in the AH (1.2 and 3.4 μg/mL, respectively) were maintained within the concentration range required for COX-2 and PEG2 inhibition, even at the end of 3h.…”
Section: Discussionmentioning
confidence: 99%
“…Hesperetin is extensively metabolized by phase II enzymes to form sulfate and glucuronide conjugates, resulting in exceedingly low bioavailability after oral administration (Brand et al, 2008(Brand et al, , 2010. Recent studies have indicated that phase II conjugates of hesperetin retain the biologic activities of the parent molecule (Takumi et al, 2012;Yang et al, 2012). This helps to explain why oral hesperetin has in vivo activities despite the fact that the compound is the least bioavailable (Giménez-Bastida et al, 2016).…”
Section: Introductionmentioning
confidence: 99%